Privacy Preserving Ciphertext Policy Attribute Based Encryption - Balu, A.; Kuppusamy, K. (Recent Trends in Network Security and Applications, 2010)
Ciphertext policy attribute based encryption (CP-ABE) allows to encrypt data under an access policy. The access policy can be formed with the logical combination of attributes.. Such ciphertexts can be decrypted by anyone with a set of attributes that satisfy the access policy. In CP-ABE, access policy is sent along with the ciphertext. We propose a method in which the access policy need not be sent along with the ciphertext, by which we are able to preserve the privacy of the encryptor. The proposed construction is provably secure under Decision Bilinear Diffe-Hellman assumption.